2018
DOI: 10.1182/bloodadvances.2018023069
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of inherited blood disorders and associations with malaria and anemia in Malawian children

Abstract: In sub-Saharan Africa, inherited causes of anemia are common, but data are limited regarding the geographical prevalence and coinheritance of these conditions and their overall contributions to childhood anemia. To address these questions in Malawi, we performed a secondary analysis of the 2015-2016 Malawi Micronutrient Survey, a nationally and regionally representative survey that estimated the prevalence of micronutrient deficiencies and evaluated both inherited and noninherited determinants of anemia. Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 63 publications
4
33
0
Order By: Relevance
“…Our study has several limitations. We purposely did not explore factors potentially associated with anaemia that previous studies had shown were uncommon in Malawi, such as haemoglobinopathies and parasitic infections [33,61]. We also did not include an HIV-infected population without severe anaemia against which to compare the prevalence of anaemia aetiologies and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. We purposely did not explore factors potentially associated with anaemia that previous studies had shown were uncommon in Malawi, such as haemoglobinopathies and parasitic infections [33,61]. We also did not include an HIV-infected population without severe anaemia against which to compare the prevalence of anaemia aetiologies and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. We purposely did not explore factors potentially associated with anaemia that previous studies had shown were uncommon in Malawi, such as haemoglobinopathies and parasitic infections (40, 57). We also did not include an HIV-infected population without severe anaemia against which to compare the prevalence of anaemia aetiologies and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although we present limited information on concomitant genetic blood disorder or hemoglobinopathy variants and anemia, a number of studies show the association between anemia and various genetic blood disorders . Among the two countries that assessed genetic variants, more than half of children with anemia had an inherited blood disorder or variant.…”
Section: Discussionmentioning
confidence: 96%